Impact Of Menstrual Practices on The Health of Adolescent Girls and The Challenges Faced in Menstrual Hygiene Management at Schools - Pratibha S; Ayesha S Nawaz; Aswin Kumar (Medsci Publications, 2016)
Introduction: Menstrual hygiene is a neglected subject in schools & lack of adequate facilities to manage it makes the adolescent girls vulnerable to reproductive tract infections. Hence this study was carried out to know the practices related to menstrual hygiene followed by the adolescent girls, impact of these practices on their physical health and challenges faced by them in managing menstrual hygiene at school. Methods: This School based cross sectional study was carried out among 346 adolescent school girls using a predesigned pretested questionnaire. Physical examination was carried out for all study subjects and Hb estimation was done for those with pallor. Results: Only 53.8% of the girls were using sanitary napkins, 37.6% of the girls changed the absorbent every six hours and 78.9% of the girls maintained hygiene of the genitalia. Symptoms of RTI were found to be high among adolescents using cloth as absorbent & those not maintaining hygiene of genitalia. Lack of satisfactory facilities to manage menstrual hygiene at school contributed to absenteeism, difficulty in concentration and poor performance among the adolescents. Conclusion: This study reinforces the crucial role of menstrual hygiene management in preventing RTI among adolescent school girls.